Investigation of Impact Properties under Instrumented Charpy Test - Zainuddin, Hikmah; Ali, Mohd Basri; Zakaria, Kamarul Ariffin; Paijan, Lailatul Harina; Mamat, Mohd Fauzi; Abu Bakar, Mohd Hadzley (Journal of Engineering and Technological Sciences, 2024)
The Instrumented Charpy impact test is a promising method for determining a material’s impact response. Stainless steel has higher impact energy absorption capacity, high tensile, and yield strength compared to aluminum. Performance varies among grades; for instance, Aluminum 7075-T6 exceeds Aluminum 6061-T6 in tensile and yield strength. However, information regarding their energy capacity and impact signal pattern is lacking. This study investigated the impact properties using a Charpy machine, a data acquisition system, and a sensing element. Strain gauges were used to record the impact strain signal, enabling the analysis of impact duration, maximum strain, and the area under the curve. Specimens experimented include Stainless Steel 304, Aluminum Alloy 6061-T6, and Aluminum Alloy 7075-T6. The Charpy machine measures absorbed energy, while the theoretical impact energy is computed from software data. The area under the strain-time curve reflects the material energy absorption capacity. Stainless Steel 304 demonstrates superior energy absorbed, impact duration, and area under the curve, followed by Aluminum 6061-T6 and Aluminum 7075-T6. Despite higher tensile and yield strength, the inferior impact response of Aluminum 7075-T6 highlights the importance of factors like ductility, elongation, and alloy composition. Consequently, Aluminum 6061 is commonly used in the automotive industry, while Aluminum 7075 is preferred in aerospace applications.